THE SUCCESS OF SHOPEE AS THE LEADING ONLINE SHOPPING PLATFORM AMONG CONSUMERS IN MALAYSIA - Arikrishnan, Raakesh A/L; Ahmad , Rohizan Binti; Dada, Morakinyo (Electronic Journal of Business and Management, 2022)
The purpose of this study is to investigate the success of Shopee as the leading online shopping platform among consumers in Malaysia, specifically during and after the Movement Control Order (MCO). Due to the restrictions of the MCO, consumers shifted significantly toward online platforms for electronics, clothing, and food. This study focused on Shopee users aged 18-30 in Kuala Lumpur to understand the factors driving this behavior. Using a quantitative approach with a sample size of 94 participants, the research examined variables like social influence and perceived usefulness. The findings indicated that Shopee’s market leadership and success are heavily attributed to its ease of use among Malaysian consumers. Keywords: Ease of Use